Continuity of care for patients with hip fracture after discharge from rehabilitation facility - Contro, Diego; Elli, Sara; Castaldi, SIlvana; Formili, Marco; Ardoino, Ilaria; Caserta, Antonello Valerio; Panella, Lorenzo (Acta Biomedica Atenei Parmensis, 2019)
Background and aims of the work: Hip fracture is a dramatic event especially in the elderly and the return to the pre-fracture functional and social state is often difficult to achieve. In the post-acute, the intensive rehabilitation period aims to recover as much autonomy as possible to these patients, but not always its duration is sufficient to ensure an effective and lasting result in returning home, hence the need for additional rehabilitation services. Our aim was to evaluate the use of additional rehabilitation services by patients who underwent hip fracture after an intensive rehabilitation treatment period performed at our hospital. Methods: This is a retrospective cohort study. We involved patients aged 45 years and older, admitted at our intensive rehabilitation, who joined a rehabilitation program for a hip fracture. Results: Our results showed how the use of further physiotherapy is associated with the type of surgical intervention and with higher Cumulative Illness Rating Scale CIRS scores. Similarly, the loss of autonomy is associated with the type of intervention, the increase in CIRS and the duration of the physiotherapy, and negatively associated with the duration of each session. The re-hospitalizations for each cause is positively associated with CIRS and negatively associated with the further use of physiotherapy. Conclusions: Our conclusion is that rehabilitation needs a personalized schedule, because the real discriminating factor in the management of frail patients should therefore be the quality, and not the quantity (i.e. longer session), of the rehabilitative intervention prescribed.